Multi-State Survey of State Opportunity Zones Laws (Last Updated Jan. 14, 2022) - Layser, Michelle (University of Illinois at Urbana-Champaign, 2022)
This dataset provides a 50-state (and DC) survey of state-level Opportunity Zones laws, including summaries of states' Opportunity Zone tax preferences, supplemental tax preferences, and approach to Opportunity Zones conformity. Data was last updated on January 14, 2022.
Keywords: Opportunity Zones; tax incentives; state law